(untitled) (Research, Society and Development, 2021)
Objective: To analyze the educational practices carried out in Primary Health Care by medical students from public and private universities in the municipality of Maceió, in terms of planning and execution. Methods: This is an empirical study of a descriptive and exploratory nature, with a qualitative approach. Medical school students from public and private universities, inserted in Primary Care practice settings in 2019 and 2020, were interviewed. The Open Interview method was used with guiding questions and to analyze the content of the message, each sentence was considered as Units of Record. Results: 38 students were interviewed with mean age 24.81 ± 4.91 being 60.5% female, of the total 21% belonged to the tenth period of the course, 23.7% had complete or incomplete previous education, being 73.7% students from a private institution. It was possible to identify the following categories "Developed Educational Actions", "Educational Resources"; "Integration, Teaching, Service and Community"; "Teamwork"; "Health Prevention"; "Self-Care"; "Benefits of Educational Actions"; "Difficulties of Educational Actions"; "Suggestions for Educational Actions". Based on the analysis of the categories, three thematic axes were highlighted: "Practical Experience", "Health Care" and "Educational Actions". Final Considerations: Through discourse analysis, this study understood the medical student’s perception about the educational practices offered in Primary Care, showing that health education provided approximation to the community’s reality, creation of a bond with users and health team, appreciation of team work and recognition of the physician’s role in this scenario.